Painful Enlarging Cervical Mass in Young Male - Jacob Lawing; Jeremy Towns; Matthew A. Heimann (Clinical Practice and Cases in Emergency Medicine, 2024)
Case Presentation: A 32-year-old male who recently immigrated from Kenya presented to the emergency department (ED) with a painful, enlarging, right-sided neck mass for eight weeks duration. Point-of-care ultrasound was used to reveal a large cystic mass with internal septations and numerous hypoechoic round lesions. Initial tuberculosis blood test ordered in the ED was positive with cultures ultimately growing Mycobaceterium tuberculosis. Discussion: Scrofula should be considered in the differential in patients presenting with enlarging neck masses who have epidemiological risk factors for tuberculosis.